After the Miracle: An Analysis on the Opportunity and Challenge of Freshippo - Yin, Jiayi (Transactions on Social Science, Education and Humanities Research, 2024)
Recent years have witnessed the rapid development of society as well as the sharp changes in people’s lifestyles. In China, retailing industries are facing many potential future challenges. Among many threats them, the brand Freshippo has created a miracle in marketing and promotion. This research systematically analyzes the success of Freshippo’s marketing strategies by methods of STP and 4Ps. After that, its weaknesses and potential challenges are critically evaluated. Based on the thorough analysis, feasible suggestions are eventually provided. By providing special services and updating merchandise rapidly, Freshippo has successfully created its competitiveness in services as well as in its products’ uniqueness and irreplaceability. Yet Freshippo is facing threats from high products prices and declining bricks-and-mortar, which are both making the brand less attractive to their targeting customers – middle-class in the society. In the future, Freshippo should better its supply chain management to provide products with more preferential prices. At the same time, Freshippo should put efforts into rejuvenating bricks-and-mortar to increase regulars’ stickiness to the brand. The research provides an overview with an analysis of Freshippo’s success. Effective solutions to common dilemmas of retailers are also argued in the research.